Meaningful learning to enhance conceptual understanding, engagement, and mathematical reasoning in elementary statistics education - Ema Butsi Prihastari; Wardono; Scolastika Mariani; Masrukan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Elementary school statistics education faces challenges due to students’ low conceptual understanding, often resulting from abstract and procedural teaching methods. Aims: This study aimed to examine the implementation of meaningful learning in elementary statistics, assess its effects on students’ conceptual understanding and engagement, and identify supporting and inhibiting factors. Method: A mixed-method explanatory sequential design was employed. Quantitative data were collected through perception questionnaires from 60 fifth-grade students, while qualitative data were obtained via participatory observations, semi-structured interviews, and classroom documentation involving one teacher and 15 students in a purposively selected class. Quantitative data were analyzed descriptively, and qualitative data were analyzed using the Miles and Huberman model. Results: Meaningful learning positively influenced statistics education. Mean scores were 3.42 for conceptual understanding (SD=0.51), 3.67 for material relevance (SD=0.48), 3.38 for motivation (SD=0.55), 3.25 for engagement (SD=0.62), and 3.35 for satisfaction (SD=0.58). All students (100%) agreed that the material was relevant to real-life contexts. Mini-project activities, such as the “Our Body Statistics” project, enhanced active participation. Supporting factors included teacher creativity, student enthusiasm, and a supportive learning environment; inhibiting factors included time constraints, varied student readiness, and limited contextual resources. Conclusion: Implementing meaningful learning improves conceptual understanding and engagement in elementary statistics. Contextual, experience-based approaches should be expanded with adequate teacher training and time allocation to optimize learning outcomes.